Penerapan Keamanan AES-256 Pada Sistem Kehadiran Karyawan Berbasis Kordinat - Dani Yusuf; Uus Rusmawan (Journal of Informatic and Information Security, 2025)
The development of information technology has encouraged the implementation of coordinate-based employee attendance systems to improve accuracy and minimize fraud in attendance recording. However, this system poses security risks to sensitive data, such as employee identities, attendance timestamps, and location coordinates. Therefore, a reliable data security mechanism is required. This study aims to implement the Advanced Encryption Standard (AES) algorithm with a 256-bit key length in a coordinate-based employee attendance system to enhance data security. The research method used is an experimental method consisting of requirement analysis, system design, implementation of the AES-256 algorithm, and system testing stages. The results show that the implementation of AES-256 is able to encrypt attendance data effectively so that the data cannot be directly read without a decryption process. In addition, the encryption and decryption processes do not have a significant impact on system performance. Thus, the AES-256 algorithm can be effectively applied to improve security in coordinate-based employee attendance systems.